2013
DOI: 10.1111/1574-6968.12171
|View full text |Cite
|
Sign up to set email alerts
|

Application of BRED technology to construct recombinant D29 reporter phage expressing EGFP

Abstract: Bacteriophage Recombineering of Electroporated DNA (BRED) has been described for construction of gene deletion and point mutations in mycobacteriophages. Using BRED, we inserted a Phsp60-egfp cassette (1143 bp) into the mycobacteriophage D29 genome to construct a new reporter phage, which was used for detection of mycobacterial cells. The cassette was successfully inserted and recombinant mycobacteriophage purified. DNA sequencing of the cassette did not show any mutations even after several phage generations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The Bacteriophage Recombineering of Electroporated DNA (BRED) technique was recently developed to generate specific mutations, insertions, deletions and gene replacement in lytic mycobacteriophage (4,6). BRED exploits a phage recombinase to induce homologous recombination (5,7–10) between a phage genome and a template, which must be electroporated into the cell (5).…”
Section: Introductionmentioning
confidence: 99%
“…The Bacteriophage Recombineering of Electroporated DNA (BRED) technique was recently developed to generate specific mutations, insertions, deletions and gene replacement in lytic mycobacteriophage (4,6). BRED exploits a phage recombinase to induce homologous recombination (5,7–10) between a phage genome and a template, which must be electroporated into the cell (5).…”
Section: Introductionmentioning
confidence: 99%
“…First, a derivative of phage L5 that carries the firefly luciferase gene was constructed by crossing over from a plasmid and identifying the recombinants by hybridization (165); these infect both fast- and slow-growing mycobacteria (195). Second, a reporter phage derivative of D29 has been constructed carrying green fluorescent protein (GFP) using recombineering (196). These approaches are more directed than using shuttle phasmids but contribute toward a suite of strategies for using phages to deliver DNA efficiently to mycobacterial hosts.…”
Section: Applications For Mycobacterial Geneticsmentioning
confidence: 99%
“…Reporter phages have been built using a variety of phage genomes including TM4, D29, and L5, all of which can infect both M. smegmatis and M. tuberculosis (165, 188, 196, 226); the TM4 platform may offer some advantages because of its ability to infect stationary-phase cells, a phenomenon that is dependent on the peptidoglycan hydrolytic motif embedded within the phage Tapemeasure protein (106). The main difference in the choice of the reporter is the detection method used.…”
Section: Applications For Mycobacterial Geneticsmentioning
confidence: 99%
“…81 The hsp60 promoter and EGFP cassette also showed detectable uorescence levels when transferred to mycobacteriophage D29 and used to infect M. smegmatis. 82 Another study showed that addition of a Strep-tag II fusion to the phAE87:hsp60-EGFP gp9 C-terminus enabled affinity purication of host bacterial complexes. 83 One study involved the development of a uorescent mycobacteriophage assay with a 100 fold increase in uorescence per cell over phAE87:hsp60-EGFP.…”
Section: Fluorescent Protein Expressionmentioning
confidence: 99%